Perubahan Kimia dan Sensoris Buah Salak Pondoh Selama Penyimpanan dalam Termodifikasi - Suhardi Suhardi; Tranggono Tranggono; Umar Santosa (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Salak pondoh (Salacca edulis RENW cultivar Pondoh) is an exotic fruit of Indonesia which is prospective as an export commodity. However, the problem is that the fruit has a short shelf life. The purpose of the investigation was to prolong the shelf life of the produce by storing them in a modified atmosphere (MA). The composition of MA was 02, 1-3% ; CO2, 0-6% and N2, 91-99% ; the storage temperature was 25°C. The results suggested that the best composition of MA was 02, 3% ; CO2, 6%, and N2, 91%. The optimum temperature for the storage was 25°C. After storage for 42 days at gives condition the fruit was still edible and in a good appearance. At contrast, the control samples deteriorated before 14 days storage.